Source of energy intake of Papuan and non-Papuan high-school students in Jayapura: their association with risk for overweight/ obesity - Endah Sri Rahayu; Bernadette Josephine Istiti Kandarina; Madarina Julia (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2020)
Background: The worldwide prevalence of obesity is increasing. Obesity is associated with many factors, including the consumption pattern of energy-producing food, i.e. carbohydrate and fat, which is, most likely associated with ethnicity. In Riskesdas 2007, Jayapura held the highest prevalence of obesity in adults in Indonesia. Jayapura lived the Papuan and Non-Papuan descents population. Objective: To determine the association between energy intake, the contribution of carbohydrate and fat to energy intake in overweight/ obesity in Papuan and non-Papuan high-school students. Methods: This cross-sectional study involved 150 Papuan and 150 non-Papuan students from three high schools in the district. Body mass index (BMI) derived from the measurement of body weight and height were grouped into overweight/obesity and not-overweight/ obesity. Source of energy was estimated using 3 (three) days non-consecutive 24 hours of food recall questionnaire. Energy intake and the contribution of carbohydrate and fat to energy intake were analyzed with an independent t-test and Chi-Square test. Results: The prevalence of overweight/ obesity was similar between Papuan and non-Papuan students (22.0 vs. 23.0%). The two groups had a similar amount of energy intake, however, the contribution of carbohydrate and fat to the total energy intake was significantly different. Obese/ overweight students had a significantly higher intake of energy, however, within the same ethnic group, the contribution of carbohydrate and fat in obese/ overweight students did not significantly differ. Conclusions: High energy intake was associated with overweight/obesity in both groups. The contribution of carbohydrates to total energy intake was higher in Papuan. However, the contribution of carbohydrate and fat to energy intake was not associated with overweight/ obesity in both groups.